In vitro and in silico anthelmintic and antibacterial activity of Rubus ellipticus leaf extracts - Deepak Kumar; Adarsh Kumar; Ankit Kumar Singh; Harshwardhan Singh; Pradeep Kumar (Discover Chemistry)
Abstract Background Bacterial and helminthic evolution has resulted in a shocking development of antibiotic and anthelminthic resistance. Medicinal plants provide an encouraging source to develop new antibacterial and anthelmintic agents. Rubus ellipticus has been employed traditionally for medicinal purposes, yet its ability against microbial resistance remains to be unraveled. Methods The present work assessed the antioxidant, antibacterial, and anthelmintic activities of leaf extracts of R. ellipticus. Antioxidant activity was measured using DPPH, antibacterial activity was done with the serial dilution technique, and anthelmintic activity was performed by using Indian earthworms. Molecular docking experiments were also carried out by utilizing Maestro 12.7 (Schrodinger) in order to screen the interaction between phytoconstituents with bacterial as well as helminthic targets. Results The methanol extract exhibited the highest antioxidant activity (%RSA = 90.95 ± 0.47%) and was the most potent antibacterial, with a minimum inhibitory concentration (MIC) value of 12.5 µg/mL against Bacillus subtilis and Escherichia coli. Paralysis and death time of earthworms were significantly reduced by methanol and acetone extracts at 20 mg/mL (paralysis: 12 ± 1.00 min, death: 15.33 ± 1.20 min). The molecular docking outcomes showed that kaempferol, ellagic acid, gallic acid, rutin, anthocyanin, and quercetin had good binding affinities towards the target proteins. Conclusion The results indicated that R. ellipticus is a potential natural source of bioactive compounds with antibacterial and anthelmintic activity. Additional research, including in vivo and mechanistic studies, is suggested to confirm its therapeutic uses.